Adipocyte progenitor cells initiate monocyte chemoattractant protein-1-mediated macrophage accumulation in visceral adipose tissue - Jennifer L. Kaplan; Melissa A. Marshall; Chantel C. McSkimming; Daniel B. Harmon; James C. Garmey; Stephanie N. Oldham; Peter Hallowell; Coleen A. McNamara (Elsevier, 2015)
Objective: Macrophages are important producers of obesity-induced MCP-1; however, initial obesity-induced increases in MCP-1 production precede M1 macrophage accumulation in visceral adipose tissue (VAT). The initial cellular source of obesity-induced MCP-1 in vivo is currently unknown. Preliminary reports based on in vitro studies of preadipocyte cell lines and adherent stroma-vascular fraction cells suggest that resident stromal cells express MCP-1. In the past several years, elegant methods of identifying adipocyte progenitor cells (AdPCs) have become available, making it possible to study these cells in vivo. We have previously published that global deletion of transcription factor Inhibitor of Differentiation 3 (Id3) attenuates high fat diet-induced obesity, but it is unclear if Id3 plays a role in diet-induced MCP-1 production. We sought to determine the initial cellular source of MCP-1 and identify molecular regulators mediating MCP-1 production. Methods: Id3+/+ and Id3−/− mice were fed either a standard chow or HFD for varying lengths of time. Flow cytometry, semi-quantitative real-time PCR, ELISAs and adoptive transfers were used to assess the importance of AdPCs during diet-induced obesity. Flow cytometry was also performed on a cohort of 14 patients undergoing bariatric surgery. Results: Flow cytometry identified committed CD45−CD31−Ter119−CD29+CD34+Sca-1+CD24− adipocyte progenitor cells as producers of high levels of MCP-1 in VAT. High-fat diet increased AdPC numbers, an effect dependent on Id3. Loss of Id3 increased p21Cip1 levels and attenuated AdPC proliferation, resulting in reduced MCP-1 and M1 macrophage accumulation in VAT, compared to Id3+/+ littermate controls. AdPC rescue by adoptive transfer of 50,000 Id3+/+ AdPCs into Id3−/− recipient mice increased MCP-1 levels and M1 macrophage number in VAT. Additionally, flow cytometry identified MCP-1-producing CD45−CD31−CD34+CD44+CD90+ AdPCs in human omental and subcutaneous adipose tissue, with a higher percentage in omental adipose. Furthermore, high surface expression of CD44 marked abundant MCP-1 producers, only in visceral adipose tissue. Conclusions: This study provides the first in vivo evidence, to our knowledge, that committed AdPCs in VAT are the initial source of obesity-induced MCP-1 and identifies the helix-loop-helix transcription factor Id3 as a critical regulator of p21Cip1 expression, AdPC proliferation, MCP-1 expression and M1 macrophage accumulation in VAT. Inhibition of Id3 and AdPC expansion, as well as CD44 expression in human AdPCs, may serve as unique therapeutic targets for the regulation of adipose tissue inflammation.